2016
DOI: 10.1590/s0102-865020160030000008
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of β-glucan against cisplatin side effects on the nervous system in rats 1

Abstract: Cisplatin has severe neurotoxic effects in rats and βg supplementation has significant beneficial effects against CP toxicity depending on its antioxidant properties. Thus, it appears that βg might be useful against CP toxicity in patients with cancer in terms of nervous system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 30 publications
3
20
0
Order By: Relevance
“…The origin of β‐glucan is organic complex molecules which obtained from cereal and yeast species (Kaya, Ciftci, Cetin, Tecellioglu, & Basak, ). Previous studies have shown that β‐glucan has various activities, such as immunomodulation and anti‐oxidation (Dietrich‐Muszalska, Olas, Kontek, & Rabe‐Jablonska, ).…”
Section: Introductionmentioning
confidence: 99%
“…The origin of β‐glucan is organic complex molecules which obtained from cereal and yeast species (Kaya, Ciftci, Cetin, Tecellioglu, & Basak, ). Previous studies have shown that β‐glucan has various activities, such as immunomodulation and anti‐oxidation (Dietrich‐Muszalska, Olas, Kontek, & Rabe‐Jablonska, ).…”
Section: Introductionmentioning
confidence: 99%
“…The clinical usage of CP is restricted due to its severe dose‐dependent side effects (Bayindir et al, ; Eid, Abdelkader, Abd El‐Raouf, Fawzy, & El‐Denshary, ). Previous research showed that CP treatment caused damage to many tissues and organ systems, such as reproductive toxicity (Kaya et al, ), nephrotoxicity (Masuda, Inoue, Miyata, Mizuno, & Nanba, ), hepatotoxicity (Ciftci, Onat, & Cetin, ), ototoxicity (Bayindir et al, ), ocular toxicity (Taşlı et al, ) and neurotoxicity (Kaya, Ciftci, Cetin, Tecellioğlu, & Başak, ). Many previous studies on CP‐induced male reproductive system toxicity demonstrated that CP administration led to oxidative damage and apoptosis in testicular tissue, a decline in testes' weight, an increase in abnormal sperm rate and a decrease in sperm concentrations and motility (Aksu et al, ; Ciftci et al, ; Kaya et al, ; Saral et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…(1 → 3)‐β‐D‐glucan is one of the antioxidant agents which possess therapeutic value in alleviating various organ injuries (Şener, Ekşioğlu‐Demiralp, Çetiner, Ercan, & Yeğen, ). Besides, (1 → 3)‐β‐D‐glucan reduces the side effects of various chemotherapy drugs (Kaya, Ciftci, Cetin, Tecellioğlu, & Başak, ; Schwartz & Hadar, ). However, in our study, instead of suppressing the toxic side effects of bortezomib, (1 → 3)‐β‐D‐glucan enhances its toxicity by decreasing the antioxidant enzyme levels, increasing the immunoreactivity of NF‐κB, and causes histopathological changes in the rat testis.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al observed that (1 → 3)‐β‐D‐glucan reduced LPO levels in their work (Wang et al, ). Kaya, Ciftci, Cetin, Tecellioğlu, & Başak demonstrated that chemotherapy drug administration with (1 → 3)‐β‐D‐glucan reduced the level of LPO and neurotoxicity (Kaya et al, ). Similarly, Erkol et al showed that beta‐glucan decreased LPO levels and liver damage (Erkol et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation